2011
DOI: 10.1111/j.1365-2036.2011.04857.x
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in phenotype and disease course in adult and paediatric inflammatory bowel disease - a population-based study

Abstract: SUMMARY BackgroundFew studies have compared phenotype and disease course in children and adults with inflammatory bowel disease (IBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 21 publications
(43 reference statements)
3
96
1
4
Order By: Relevance
“…The predominance of extensive disease in our cohort is in agreement with data from most contemporary pediatric cohorts. 10,11,31,33 The previously reported difference in disease extension between childhood-and adulthood-onset UC was Variables with a P-value .0.05 in univariate analysis were not included in the multivariate analysis except for sex and age that were considered to be potential confounding factors. Statistically significant hazard ratios (P , 0.05) are bolded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominance of extensive disease in our cohort is in agreement with data from most contemporary pediatric cohorts. 10,11,31,33 The previously reported difference in disease extension between childhood-and adulthood-onset UC was Variables with a P-value .0.05 in univariate analysis were not included in the multivariate analysis except for sex and age that were considered to be potential confounding factors. Statistically significant hazard ratios (P , 0.05) are bolded.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Data from these studies suggest that childhood-onset IBD is characterized by more extensive intestinal involvement at diagnosis. During the last decade, several studies have been published, which describe the early disease course of patients with childhood-onset IBD.…”
mentioning
confidence: 96%
“…Inflammatory bowel disease (IBD) is diagnosed before the age of 18 years in approximately 25% of all patients; approximately one-quarter of all affected children and adolescents are under the age of 10 years at diagnosis (3). Children and adolescents with IBD are more likely to have more severe intestinal involvement at diagnosis and faster disease progression than adults (4). Treatment recommendations for children and adolescents are different than those for adults (5-13, e1).…”
mentioning
confidence: 99%
“…Chouraki et al stratified patients into two age groups (0–9 years and 10–19 years) and also reported an obvious increase of IBD in older children and a slight increase in younger children comparing incidence rate of IBD in 1988–1990 and in 2006-2007 [6]. In contrast with these findings, Jakobsen et al did not observe difference in incidence rates over a 12-year period (1998–2009) after stratifying the patients into three 5-year age groups (0–4 years, 5–9 years, and 10–14 years) [48]. The only report describing a significantly rising incidence of IBD patients younger than 5 years came from Ontario, Canada [37].…”
Section: Incidence Rates In Childhood In Different Age Groupsmentioning
confidence: 99%